Sintetis Senyawa Caffeic Acid Phenethyl Ester dan Karakterisasinya Menggunakan 1H NMR - La Ode Kadidae (SAINS : Jurnal Kimia & Pendidikan Kimia, 2021)
Thesynthesis ofcaffeic acid phenethyl ester (CAPE) and its characterization using 1H NMR has been carried out. This research aims to discloseseveral potential ways of CAPE synthesis.The study was conducted by reacting some precursors in effort to produce CAPE.The progress of the synthesis was monitored using TLC and the characterization of the synthetic products was performed with 1H NMR.Three different approaches in effort to synthesize CAPE were conducted.The first approach was a direct rection between caffeoyl chloride and phenethyl alcohol. The second approach was including a protection using benzyl group and the last one was utilizing acetyl protecting groups where both these protecting groups were used to protect the catechol groups of the caffeic acidmoiety. However, the first and second methods failed to achieve the compound target, CAPE. There was only one procedure hasbeen successful, namely the reaction between phenethyl ester with acetyl-protected caffeic acidresulting inthe production of the synthetic compound target, CAPE, as much as 42%